Produtividade de milho para silagem em integração lavoura-pecuária-floresta - Santos, Emanuelle Beatriz Cruz e (2014)
Food production is derived from monocultures that have shown low sustainability. Corn crops present high dry matter production with flexible use. Integrated systems are the means of production involving agriculture, livestock and forest, being necessary to define a point of optimal balance in which all cultures develop properly. Two independent experiments were performed, maize intercropped with Piata grass maize intercroped with ruziziensis. Thus, the aim was evaluate the corn to silage intercropped to piatã and ruziziensis grass in different seeding rates of grass under sun and shadow conditions. This experiment was carried out at Embrapa, Sinop/Mato Grosso, Brazil. Two corn row spacings was tested (45 and 90 cm), intercropped with piatã and ruziziensis grass under four seeding rates (0, 2, 4 and 6 kg PSV/ha). The treatments had distribution in randomized complete blocks in factorial arrangement with four replications at two light environments. The evaluations were: corn dry matter production, piatã grass production and total production; plant height and ear insertion height; plant end stand; stem diameter; stay-green and composition of corn plant was carried out with the separation in dry leaves, green leaves, stems, bracts, cobs and grains. For intercropping maize with grass Piata, the total production of dry matter in the sun was 41% greater than in the shadow, whereas the lightness was reduced 100 to 70%. The restricted light promoted descent of 30% in corn production. The row spacing of 90 cm increased the grass dry matter production when compared to 45cm. The shading affected corn productivity whereas row spacings that promoted better plant distribution favoured intercropped in these conditions. By intercropping maize with ruziziensis, the row spacing of 45 cm resulted in an increase of 7% of total DM yield of maize and MS compared to 90 cm. The DM yield of grass ruziziensis was 50% bigger at full sun than under shade. The row spacing of 45 cm between rows of corn resulted in higher productivity of grass ruziziensis. Corn grown for silage ruziziensis intercropped with grass and trees did not cause a significant drop in production, being denser than the spacing between rows of maize resulted in an increase in productivity.